Perspective of Traditional Birth Attendants on Their Experiences and Roles in Maternal Health Care in Rural Areas of Northern Ghana - Adatara, Peter; Afaya, Agani; Baku, Elizabeth A.; Salia, Solomon Mohammed; Asempah, Anthony (International Journal of Reproductive Medicine, 2018)
Background. Traditional birth attendants play significant roles in maternal health care in the rural communities in developing countries such as Ghana. Despite their important role in maternal health care, there is paucity of information from the perspective of traditional birth attendants regarding their role on maternal health care in rural areas in Ghana. Objective. The aim of this study was to explore and describe the role of traditional birth attendants in maternal health care in the rural areas in Ghana. Methods. A qualitative explorative approach was adopted to explore the role of traditional birth attendants in maternal health care in the rural areas of Ghana. Ten (10) out of a total of twenty-seven (27) practising traditional birth attendants in the study area were purposefully selected from five (5) rural communities in the Bongo District of Ghana for the study. Data were collected through in-depth, unstructured, individual interviews using a guide. Data collected from the interviews were transcribed verbatim and analysed to identify themes. Results. Six main roles of traditional birth attendants on maternal health care in rural areas were identified in this study: traditional birth attendants conduct deliveries at home, they provide health education to women on nutrition during pregnancy and lactation, they arrange means of transport and accompany women in labour to health facilities, they provide psychological support and counselling to women during pregnancy and childbirth, and traditional birth attendants are not paid in cash for the services they render to women in the rural areas. Conclusion. Our study brought to light the critical role traditional birth attendants play in maternity in rural and remote areas in Ghana. There is a need for skilled birth attendants to collaborate with traditional birth attendants in rural and deprived communities to provide quality and culturally accepted care in the rural communities.